Trade, Inequality, and the Political Economy of Institutions - Do, Quy-Toan; Levchenko, Andrei A. (2012)
This paper investigates the relationship between international trade and the quality of economic institutions. We model institutions as fixed costs of entry, in a framework that has two key features. First, preferences over entry costs differ across firms and depend on firm size. Larger firms prefer to set higher costs of entry, in order to reduce competition. Second, these costs are endogenously determined in a political economy equilibrium. Trade opening can lead to higher entry costs when it changes the political power in favor of a small elite of large exporters, who in turn prefer to install high entry barriers.